Experimental and theoretical studies of jet noise phenomena - Sperry, Willard Charles; Peter, A.; Kamo, R.; Armour Research Foundation (U.S.); United States. Air Force. Systems Command. Aeronautical Systems Division (Wright-Patterson Air Force Base, Ohio : Directorate of Materials and Processes, Aeronautical Systems Division, Air Force Systems Command, United States Air Force, 1962)
Over-all sound pressure levels were measured in an anechoic room for noise generated by cold air flow through more than twenty different nozzle configurations including converging, converging-diverging, slot, and annular types, the latter with and without center core flow. The results are examined in terms of over-all acoustic power and directivity versus mass flow and compared with various eighth power relations. The acoustic performance of most nozzles was similar in the subsonic region. However, certain annular type nozzles exhibited a marked superiority in the supersonic region. Theoretical discussions are presented concerning the generation of sound and the relationship between various turbulence and statistical theories. A modified mixing length theory is developed showing its application to turbulence generation as well as its influence on the general forcing function equation. Temperature effects are included. Empirical data are given pertaining to the correlation of jet noise from circular and annular nozzles. (Author).
Photo reproduction.
"June 1962."
Includes bibliographic references (pages 160-163)
Research supported by the United States Air Force, Air Force Systems Command, and performed by Armour Research Foundation of Illinois Institute of Technology, Chicago, Illinois, under contract no.
Mode of access: Internet.
Keywords: Jet nozzles; Exhaust nozzles; Jet planes -- Noise